Dynamic monitorization of structures with optical sensors - Antunes, P. (2012)
Fiber optical sensors, namely Fiber Bragg gratings, are one the most promising technologies in several sensing systems. This sensing technology could be useful and cost effective in most civil engineering infrastructures. FBG sensors take advantage of the optical fiber properties, such us low transmission losses, immunity to electromagnetic interference, light weight and electrical isolation. But also, since the information is codified in the optical domain, they can be used in hostile environments, where electrical currents of electronic devices might pose a hazard. In this work we proposed the application of optical FBG based accelerometers to monitor two structures: a reinforced concrete building and a steel footbridge. The results show that optical monitoring schemes can be used in structural health monitorization of large structures, being a low cost solution. The two implemented acceleration systems, with different interrogation techniques allow to successfully obtaining the eigenfrequencies of structures with an error, when compared with the value obtained with a reference electronic accelerometer inferior to 0.80 %.